Regulation of cross-border establishment in China and the EU : a comparative law and economics approach / Guang Shen. - Shen, Guang (Ius commune europaeum, 2016)
A book series devoted to the common foundations of the European legal systems. The Ius Commune Europaeum series includes comparative legal studies as well as studies on the effect of treaties within national legal systems. All areas of the law are covered. The books are published in various European languages under the auspices of METRO, the Institute for Transnational Legal Research at Maastricht University.This book examines the regulation of the inter-provincial establishment of companies in China and the EU regulation of the cross-border establishment of companies from the perspective of comparative law and economics. Part I of this book discusses the rules governing inter-provincial establishment in China and examines their implementation, with a focus on revealing the barriers to this activity. This part also analyses the evolution of the EU internal market and shows how the EU regulates the cross-border establishment of companies.Subsequently, Part II presents an economic analysis of the regulation of the crossborder establishment of companies in a multi-level jurisdiction. In Part III, the regulation of the inter-provincial establishment of companies in China is reviewed in the light of the economic literature. With the aim of examining whether China can learn something from the EU's experience with market integration, Part III also analyses the differences between the regulation of the inter-provincial establishment of companies in China and the EU regulation of the cross-border establishment of companies.This book offers a thorough analysis of the regulation of business establishment in China and, more generally, the law and economics literature on business licensing. Therefore, it is of interest for law and economics scholarship, companies doing business in China and policy makers responsible for regulating business establishment.